Dialogic critical reading in smart classrooms: IRF configurations and student response quality - Utomo, Asep Purwo Yudi; Ngabiyanto; Wijayanti, Tutik; Feriady, Muhammad; Kesuma, Rossi Galih; Kumalasari, Riri (Research Journal in Advanced Humanities, 2026)
Critical reading in technology-rich classrooms depends not only on access to digital texts but also on how classroom talk organizes interpretation, evidence, and evaluation. This study maps Initiation-Response-Feedback (IRF) configurations in 260 interaction units observed across five higher-education classes and seven meetings in a smart-classroom setting. A descriptive qualitative classroom discourse analysis coded each unit for structural configuration, initiation, response, feedback, participation, and response quality. Frequencies describe corpus tendencies and do not test causal relationships. Complete IRF was the most frequent configuration (50.38%), while IRFR (22.31%) and repeated IRF (16.15%) documented substantial exchange extension. Reflective/open initiation was the leading initiation function (33.85%); reflective and elaborative responses together accounted for 84.62% of the corpus. Elaborative expansion was the most frequent feedback function (46.92%), and 85.77% of units showed moderate or active participation. Representative sequences indicate that IRF became more dialogically productive when follow-up moves reopened the exchange, returned students to textual evidence, and prompted comparison or revision. Shared displays and annotations served as contextual resources in selected sequences, but technology was not analyzed as an independent causal factor. The study operationalizes dialogic expansion as a lens for distinguishing structurally complete exchanges from those that increase students' epistemic work. It also reframes the smart classroom as an interactional context whose pedagogical value depends on lecturer interactional competence.